Analisis (kimochi, kibun, dan kigen ) dalam Novel Kitchin Karya Banana Yoshimoto: Kajian Sintaksis dan Semantik - Aprilani, Felicia (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2019)
In this study the authors analyzed the form and function of expressions of heart in Japanese kimochi, kibun and kigen. The purpose of this study is to discrete the form and function of kimochi, kibun and kigen in the sentence contained in Banana Yoshimoto's kitchin novel through the study of form and function. In this study the author uses descriptive analysis method according to Sudaryanto's theory. According to the method of descriptive analysis is research carried out solely based on facts or phenomena that are empirically used by speakers so that it can be presented as is. For data analysis, the writer uses the method, namely the basic technique for Direct Elements (BUL). To analyze the data, the author uses the theory of Kyosuke Kandaichi and his friends. Based on the theory, it can be known the function of kimochi noun, kibun and kigen is to express the element of feeling that has the characteristics of each.